Pneumatic classification of coal in bottom-fluidized transport column - Zhong, L.; Zhong, M.; Dong, Li; Zhang, J.; Ma, F.; Xu, G. (Zhongguo Huagong Xuehui, 2011)
This work was devoted to investigating the pneumatic classification behavior of coal particles(0-10 mm) in a bottom-fluidized transport column. The tested influence parameters included superficial gas velocity of transport column, dimensionless velocity of particles, coal feeding position and rate, and internal baffle in the fluidized bottom. The classification performance was analyzed by measuring the amounts and size distributions of the elutriated particles, overflowed particles from the fluidized bed and the particles remaining in the bottom of the column. The Newton classification efficiency was used to quantitatively evaluate the classification performance. The results showed that there was an optimal dimensionless velocity for separating the fraction of particles below a given size via entrainment. With the increase of the targeted size, the Newton classification efficiency increased but the corresponding optimal dimensionless velocity gradually decreased. Feeding coal from a higher position and at lower rates facilitated the classification for small-size particles(via elutriation). The elutriated particle amount and the classification efficiency for a fraction below a given size both decreased when inserting a vertical baffle in the fluidized particles at the column bottom. © All Rights Reserved.